2017
DOI: 10.1007/s11604-017-0717-9
|View full text |Cite
|
Sign up to set email alerts
|

Grading system to categorize breast MRI using BI-RADS 5th edition: a statistical study of non-mass enhancement descriptors in terms of probability of malignancy

Abstract: The three-grade criteria and categorization by sum-up grades of descriptors appear valid for non-mass enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
26
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 17 publications
8
26
3
5
Order By: Relevance
“…[13][14][15][16][17][18] When malignant and benign lesions were compared in regard to distribution and internal enhancement couples, we found that lesions with segmental distribution along with clustered-ring enhancement were significantly associated with malignancy (p < 0.05). This finding was also reported in a study by Asada et al 19 We also found a significant relationship between malignancy and diffuse distribution (p < 0.05); however, this may have been due to the low number of cases with diffuse distribution. The most frequent distribution types in our study were focal (31%) and linear (28.7%) distribution which were not associated with malignancy (p > 0.05).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[13][14][15][16][17][18] When malignant and benign lesions were compared in regard to distribution and internal enhancement couples, we found that lesions with segmental distribution along with clustered-ring enhancement were significantly associated with malignancy (p < 0.05). This finding was also reported in a study by Asada et al 19 We also found a significant relationship between malignancy and diffuse distribution (p < 0.05); however, this may have been due to the low number of cases with diffuse distribution. The most frequent distribution types in our study were focal (31%) and linear (28.7%) distribution which were not associated with malignancy (p > 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, various studies have reported a lack of association between malignancy and homogeneous pattern and very low PPV values. 16,19,21,22,25 The most frequent dynamic curve type among malignant lesions was Type II curve (with a PPV of 34.1%) in the current study. In a study by Yang et al, the most frequent curve type among malignant lesions was also reported as Type II curve; however, their PPV of 74.1% was significantly higher than our result.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…A branching line with the size of 1 cm or more was significantly more frequently associated with malignancy than a single line smaller than 1 cm [31]. Linear distribution with single line pattern smaller than 1 cm was recommended to be assigned to the BI-RADS 3 category [31,40]. Consistent with results from a previous study [23], 30.4% of non-calcified DCIS presenting as NME lesion showed the persistent enhancement.…”
Section: Discussionsupporting
confidence: 80%
“…Yang ve arkadaşları en fazla internal kontrastlanmanın halkasal patern olduğunu, PPD'sinin de %79.3 olduğunu rapor etmiştir (14). Genel olarak en fazla internal kontrastlanmanın halkasal patern olduğu ve malignite ile ilişkili olduğu ifade edilmiştir (6,15,(18)(19)(20). Kümelenmiş noktasal ve heterojen kontrastlanmanın ise malignite ile orta düzeyde ilişkili olduğu, kümelenmiş noktasal paternin PPD'lerinin de bizim sonuçlarımıza benzer şekilde %20 ile %32.8 arasında değiştiği rapor edilmiştir (6,21,22).…”
Section: Discussionunclassified